2016
DOI: 10.1016/j.antiviral.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of treatment-resistant infectious HIV after genome-directed antiviral endonuclease therapy

Abstract: Incurable chronic viral infections are a major cause of morbidity and mortality worldwide. One potential approach to cure persistent viral infections is via the use of targeted endonucleases. Nevertheless, a potential concern for endonuclease-based antiviral therapies is the emergence of treatment resistance. Here we detect for the first time an endonuclease-resistant infectious virus that is found with high frequency after antiviral endonuclease therapy. While testing the activity of HIV pol-specific zinc fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 58 publications
0
46
0
Order By: Relevance
“…The induced insertions and deletions introduced into the viral target site may not themselves result in a loss of viral fitness if they maintain the frame of the encoded protein, as illustrated by insertion of a tyrosine after a 3 bp insertion into the viral reverse transcriptase after ZFN therapy. 25 Similar resistance mutants have been shown to emerge and replicate in cultures undergoing treatment with HIV-targeted Cas9. [26][27][28] Fortunately, it appears that the emergence of resistance can be successfully managed in a manner that is analogous to traditional antiviral therapy, by simultaneously targeting multiple sites within the viral genome.…”
Section: Resistancementioning
confidence: 91%
“…The induced insertions and deletions introduced into the viral target site may not themselves result in a loss of viral fitness if they maintain the frame of the encoded protein, as illustrated by insertion of a tyrosine after a 3 bp insertion into the viral reverse transcriptase after ZFN therapy. 25 Similar resistance mutants have been shown to emerge and replicate in cultures undergoing treatment with HIV-targeted Cas9. [26][27][28] Fortunately, it appears that the emergence of resistance can be successfully managed in a manner that is analogous to traditional antiviral therapy, by simultaneously targeting multiple sites within the viral genome.…”
Section: Resistancementioning
confidence: 91%
“…De Silva Feelixge et al (2016) were the first to demonstrate that viral resistance can occur following endonuclease therapy. They showed that an insertion mutation introduced into the HIV provirus following ZFN therapy enabled virus replication and ZFN cleavage resistance.…”
Section: Hurdles To Human Applicationmentioning
confidence: 99%
“…Although the high reverse transcriptase error rate of HIV makes the likelihood of de novo replication-derived resistance greater than for other DNA viruses, these three studies demonstrate that endonuclease-derived resistance could be a significant concern. Future studies should determine whether endonuclease resistance can occur for other viruses, and if so, whether combinations of endonucleases (De Silva Feelixge et al 2016) or sgRNAs (Kennedy et al 2015) can avoid the development of resistance.…”
Section: Hurdles To Human Applicationmentioning
confidence: 99%
“…Additional concerns such as the potential immunogenicity of gene editing enzymes, toxicity due to off-target cleavage, and the potential development of treatment resistance will need to be addressed. Indeed, one study identified a mutational insertion in a highly conserved region of pol that provided resistance to subsequent endonuclease cleavage but did not lethally mutate the virus [69]. In another study, virus escaped CRISPR/Cas9 targeting of several conserved regions of the HIV genome [70].…”
Section: Targeting the Hiv Genome Directlymentioning
confidence: 99%